2019
DOI: 10.1186/s40709-019-0102-1
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA attenuates Aβ-induced neurotoxicity by down-regulating COX-2 expression and PGE2 synthesis via inactivation of NF-κB pathway in SH-SY5Y cells

Abstract: Amyloid-β (Aβ)-induced neurotoxicity is a major pathological mechanism of Alzheimer’s disease (AD). Tanshinone IIA (Tan IIA), extracted from traditional Chinese herb Radix salvia miltiorrhiza, possesses anti-oxidant and anti-inflammatory actions, as well as neuroprotective effects. The present study aims to explore the possible mechanism by which Tan IIA attenuated Aβ-induced neurotoxicity. Exposure of SH-SY5Y cells to different concentrations of Aβ led to neurotoxicity by reducing cell viability, inducing cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Therefore, COX-2 inhibition could be useful for the treatment of esophageal cancer. Tan IIA could downregulate COX-2 expression and inactivate the NF-κB pathway in SH-SY5Y cells (39).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, COX-2 inhibition could be useful for the treatment of esophageal cancer. Tan IIA could downregulate COX-2 expression and inactivate the NF-κB pathway in SH-SY5Y cells (39).…”
Section: Discussionmentioning
confidence: 94%
“…COX-2 has been shown to be a key molecular regulator of cancer progression and metastasis and a crucial target in cancer therapy. A recent study found that tan IIA could downregulate COX-2 expression and inactivate the NF-κB pathway in SH-SY5Y cells ( 39 ). Therefore, we used molecular docking for further research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it inhibited the expression at the transcriptional and translational levels of inducible nitric oxide synthase (iNOS), matrix metalloproteinase-2 (MMP-2) and nuclear transcription factor κ (NF-κBp65) genes. Improvements in memory, reduction in AChE activity, mitigation of neuronal damage and oxidative stress, and in restoring cholinergic balance have also been observed in other studies following administration of this compound [427,428].…”
Section: Salvia Sppsupporting
confidence: 62%
“…Tanshinone IIA, a lipophilic diterpene found in the Chinese traditional herb, Danshen, exhibits antioxidant, anti-inflammatory, antitumor, cardiovascular-protective, and neuroprotective effects. Tanshinone IIA reduced the production of pro-inflammatory mediators by inhibiting the NF-κB pathway, promoted the shift from M1 microglia to M2 microglia, and activated macrophage migration inhibitory factor (MIF), thereby attenuating neuroinflammation [ 108 , 109 , 110 ].…”
Section: Neuroprotective Effects Of Potential Natural Compounds Anmentioning
confidence: 99%